A Rare Case of Bilateral Radicular Cyst in Primary Maxillary Molars - Shivanna, Veena (Achievements and Challenges of Medicine and Medical Science Vol. 11, 2025)
Radicular cysts are inflammatory in origin have most predilections for permanent dentition and are seen in the anterior maxillary region. Radicular cyst constitutes only 0.5-3.5% of deciduous teeth. This case report reveals an extremely rare occurrence of bilateral radicular cysts in maxillary primary molars in a 7-year-old male patient. The patient had episodes of pain in the same region which were intermittent, localized, and mild and subsided on taking medications. Extraoral examination revealed a swelling in the left middle third of the face which was diffuse, non-tender, and bony hard. Both the cysts were enucleated one after another depending on the severity of signs and symptoms followed by extraction of deciduous teeth. A 5-month follow-up, radiograph was taken to ensure the position of succedaneous teeth. This case illustrates a common condition seen in an uncommon age group at the uncommon site.